Rethinking the Multidimensionality of Growth Mindset Amid the COVID-19 Pandemic: A Systematic Review and Framework Proposal - Ku, Yun-Ruei; Stager, Catanya (Frontiers in Psychology, 2022)
Students, staff, and faculty in higher education are facing unprecedented challenges due to the COVID-19 pandemic. Recent data revealed that a good number of academic activities and opportunities were disrupted as a result of the COVID-19 pandemic and its variants. While much uncertainty remains for the next academic year, how higher education institutions and their students might improve responses to the rapidly changing situation matters. This systematic review and framework proposal aim to update previous empirical work and examine the current evidence for the effectiveness of growth mindset interventions in young adults. To this end, a systematic search identified 20 empirical studies involving 5, 805 young adults. These studies examined growth mindset within ecologically valid educational contexts and various content areas. Generally, these findings showed that brief messages of growth mindset can improve underrepresented students' academic performance and facilitate other relevant psychological constructs. In addition, we argue, although growth mindset has been identified as a unitary concept, it is comprised of multiple interdependent skills, such as self-control, self-efficacy, and self-esteem. Understanding the nature of growth mindset may contribute to successful mindset implementation. Therefore, this article presents a practical framework to help educators in higher education rethink the multidimensionality of growth mindset and to provide their students with alternative routes to achieve their goals. Finally, additional articles were discussed to help evaluate growth mindset interventions in higher education.